Isolasi Jamur yang Berasosiasi dengan Kumbang Ambrosia pada Pohon Angsana (Pterocarpus indicus): Isolation of Fungus associated with Ambrosia Beetle on Angsana Tree (Pterocarpus indicus) - Mochammad Mirza Saputra; Laksamana Agadhia Raharjo; Mohamad Adi Wijayanto; Muhammad Qoyyimul Amri; Ika Nur Fitriana (Agrocentrum, 2023)
Insect pests are organisms that can damage plants and have a high level of damage. However, it is not only insects that need to be watched out for but also the microorganisms they carry inside and outside their bodies. These insects are referred to as vectors. Ambrosia beetle is a plant vector that carries both saprophytic and pathogenic fungi. There is little information about ambrosia beetles and the mushrooms they carry, so they need to be studied further. This study aimed to determine the fungi associated with the ambrosia beetle on Angsana trees (Pterocarpus indicus). The research used purposive sampling by examining the symptoms and signs of an ambrosia beetle attack. The identification process is based on morphological forms and entomology manuals. The results obtained based on morphological identification showed that the ambrosia beetle came from the genus Cryphalus sp. In contrast, the associated fungus comes from the genus Geosmithia sp. It is known that the fungus Geosmithia sp. can act as a pathogen so that it can damage Angsana trees.